2017
DOI: 10.1186/s13075-017-1443-5
|View full text |Cite
|
Sign up to set email alerts
|

Soluble CD40L is associated with increased oxidative burst and neutrophil extracellular trap release in Behçet’s disease

Abstract: BackgroundStudies have suggested that soluble factors in plasma from patients with active (aBD) and inactive (iBD) Behçet’s disease (BD) stimulate neutrophil function. Soluble CD40 ligand (sCD40L) is an important mediator of inflammation in BD. Its expression and effect on neutrophil oxidative burst and neutrophil extracellular trap (NET) release have not been characterized. In this study, we sought to investigate the role of plasma and the CD40L pathway on NET release and the oxidative burst profile in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
41
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 42 publications
(55 reference statements)
5
41
0
1
Order By: Relevance
“…Few studies have addressed the role of NETosis in BD. In line with our results, a recent study by Perazzio et al showed that circulating neutrophils from active BD release more NETs than those from inactive BD and healthy controls [11]. In that study, the authors performed a multiplex screening of cytokines and soluble receptors and found a number of soluble factors increased in the serum of active BD patients compared to healthy controls.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Few studies have addressed the role of NETosis in BD. In line with our results, a recent study by Perazzio et al showed that circulating neutrophils from active BD release more NETs than those from inactive BD and healthy controls [11]. In that study, the authors performed a multiplex screening of cytokines and soluble receptors and found a number of soluble factors increased in the serum of active BD patients compared to healthy controls.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, IL8 a known chemo-attractant of neutrophils, was not significantly increased in the serum of active BD [11]. This points towards distinct cytokines acting in attracting neutrophils and inducing NETosis.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…In sepsis, EC activation induced adhesion receptors, released in ammatory mediators such as interleukin(IL)-1, IL-6 and tumor necrosis factor (13,14). sCD40L also effect on neutrophil oxidative burst and neutrophil extracellular trap (5,15). Previous studies and our studies suggested that sCD40L has no correlation with other coagulation factors except tissue factor(TF) (8).…”
Section: Discussionmentioning
confidence: 56%